Information Sharing in Military Operations
XIV, 274 p. 11 illus., 4 illus. in color.
Keywords: This volume explores the interpersonal, organizational, and technological enablers and barriers to information and intelligence sharing in multinational and multiagency military, humanitarian, and counterterrorism operations. To this end the contributions present case studies and other empirical research. UN and special operations headquarters are studied, along with multinational operations in Mali, Iraq, and Afghanistan by the UN and by U.S. Central Command. Perennial themes are the need for a holistic approach to information sharing—one that incorporates all the above enablers—and the importance of learning from experience, which should be the basis for operational planning. There is still considerable ground to be gained in enhancing the efficacy of information sharing in the context of defense and security, and the present book contributes to this goal.